The relationship between obesity and obstruction risk of lateral inguinal hernia at Negara general hospital in 2019-2020 - Bharata, Bagus S.; Triarta, Gita B. (International Journal of Research in Medical Sciences, 2020)
Background: A hernia is the protrusion of the abdominal contents from the normal cavity through a defect in the fascia and aponeurotic muscle of the abdominal wall, either congenital or acquired. The hole can arise because the embryonic opening does not close or widen, due to high intra-abdominal pressure caused by chronic coughing, heavy lifting, overweight, obesity, and weakness of the abdominal wall muscles. The incidence of inguinal hernias is higher in patients with body mass index (BMI) who are overweight and obese than those with normal body weight. A study that conducted by Sneiders et al stated that each increase of 1 kg/m2 BMI would increase the risk of hernia complications by 1.03 times (p=0.03). Methods: This study used a cross-sectional analytic study. The samples were determined by consecutive sampling. In this study, the sample used was patients with a diagnosis of inguinal hernia who were divided based on the presence or absence of complications and divided according to BMI, then saw whether there was a relationship between BMI in the obesity category and the incidence of complication inguinal hernia. This study uses data from medical records at the Negara General Hospital from 2019-2020. Results: This study used 79 respondents of hernia patients at the Negara General Hospital who met the inclusion criteria and did not meet the exclusion criteria. There were 77 people (97.5%) male respondents and 2 (2.5%) female respondents with a mean age of 53.05 years (SD±19.7 years). As for the underweight body mass index there were 6 people (7.6%), normal as many as 41 people (51.9%), overweight as many as 4 people (5.1%), and obese as many as 28 people (35.4%). The diagnosis of reducible hernia was 52 people (65.8%), 21 people (26.6%) incarcerated hernia, 5 non-reducible hernias (6.3%) and 1 strangulated hernia (1.3%). Conclusions: The conclusion of this study indicates a significant relationship between BMI and the incidence of complicated hernias. Obese hernia patients were 7.2 times more likely to develop hernia complications than non-obese patients.